C[sbnd]C bond cleavage in the electrooxidation of 2,3-butanediol controlled by an ionic liquid modifier - Yang, Juntao; Haßfurther, Florian; Hilpert, Felix; Hussain, Zarah; Yang, Tian; Taccardi, Nicola; Wasserscheid, Peter; Brummel, Olaf; Libuda, Jörg (Journal of Catalysis, 2024)
In heterogeneous catalysis, ionic liquids (ILs) are used as chemical modifiers to control selectivity. In our work, we aim to apply the same concept to electrocatalytic systems. As a model reaction, we studied the electrooxidation of 2,3-butanediol on the low-index Pt(1 1 1), Pt(1 0 0) and Pt(1 1 0) surfaces in an acidic environment. We used the IL 1-ethyl-3-methylimidazolium trifluoromethanesulfonate ([C2C1Im][OTf]) dissolved in an aqueous electrolyte as a catalyst modifier. The reaction mechanisms were investigated by electrochemical infrared reflection absorption spectroscopy (EC-IRRAS). The oxidation of 2,3-butanediol is highly structure dependent. On all three surfaces, the two products formed are acetoin and diacetyl, i.e. either one or two alcohol functionalities are oxidized. However, we observe distinct features on the different surfaces with respect to activity, potential window of oxidation, and selectivity. Only the Pt(1 0 0) surface is active towards C[sbnd]C bond cleavage. The latter reaction leads to the formation of COads and poisoning of the catalyst. Modification of this surface by addition of the IL leads to an increase of the selectivity for acetoin from 51 % to 78 % (at 1.1 VRHE). In addition, C[sbnd]C bond cleavage is suppressed, no CO is formed, and the surface remains active for the target reaction. We attribute these effects to the reversible and structure dependent adsorption of the [OTf]− anions on the Pt surfaces and additional interionic interactions. Our results demonstrate the potential of ILs to control selectivity in electrocatalytic reactions.
CRIS-Team Scopus Importer:2024-05-31
Keywords: In-situ IR spectroscopy; Ionic liquids; Platinum; Secondary alcohols; Selectivity; Single crystals; Supported catalyst with ionic liquid layer

Interactions of the Ionic Liquid [C2C1Im][DCA] with Au(111) Electrodes: Interplay between Ion Adsorption, Electrode Structure, and Stability - Yang, Juntao; Hilpert, Felix; Qiu, Yunsheng; Franz, Evanie; Briega-Martos, Valentín; Cherevko, Serhiy; Mayrhofer, Karl; Brummel, Olaf; Libuda, Jörg (Journal of Physical Chemistry C, 2024)
Modification of electrocatalysts with ionic liquids (ILs) allows us to control the activity and selectivity on the one hand but also directly affects the stability of the electrode. In this work, we studied the interaction of the IL 1-ethyl-3-methylimidazolium dicyanamide [C2C1Im][DCA] with a Au(111) surface in an aqueous electrolyte (phosphate buffer, pH 7) and the impact of the IL on the electrochemical stability of the surface. We combined complementary electrochemical in situ methods, namely, electrochemical infrared reflection absorption spectroscopy (EC-IRRAS), cyclic voltammetry (CV), electrochemical scanning tunneling microscopy (EC-STM), and online inductively coupled plasma mass spectrometry. We observe the potential-dependent and reversible adsorption-desorption of ionic species on the Au(111) surface in the potential window between 0.1 and 1.1 VRHE. We identified two types of adsorbed [DCA]− species, showing different adsorption kinetics. Already at low concentrations, the IL (10 mM) enhances the dissolution during oxidation and reduction cycles by a factor of more than 40. We observe a suppressed redeposition of dissolved Au-ions in the presence of the IL due to the formation of gold complexes with the [DCA]− anions. Our result provides molecular insights into the interplay between ionic liquid-surface interactions and surface stability.
CRIS-Team Scopus Importer:2024-03-08

Mechanistic Insight into Solution-Based Atomic Layer Deposition of CuSCN Provided by In Situ and Ex Situ Methods - Hilpert, Felix; Liao, Pei-Chun; Franz, Evanie; Koch, Vanessa; Fromm, Lukas; Topraksal, Ece; Görling, Andreas; Smith, Ana-Suncana; Barr, Maissa; Bachmann, Julien; Brummel, Olaf; Libuda, Jörg (ACS Applied Materials and Interfaces, 2023)
Solution-based atomic layer deposition (sALD) processes enable the preparation of thin films on nanostructured surfaces while controlling the film thickness down to a monolayer and preserving the homogeneity of the film. In sALD, a similar operation principle as in gas-phase ALD is used, however, with a broader range of accessible materials and without requiring expensive vacuum equipment. In this work, a sALD process was developed to prepare CuSCN on a Si substrate using the precursors CuOAc and LiSCN. The film growth was studied by ex situ atomic force microscopy (AFM), analyzed by a neural network (NN) approach, ellipsometry, and a newly developed in situ infrared (IR) spectroscopy experiment in combination with density functional theory (DFT). In the self-limiting sALD process, CuSCN grows on top of an initially formed two-dimensional (2D) layer as three-dimensional spherical nanoparticles with an average size of ∼25 nm and a narrow particle size distribution. With increasing cycle number, the particle density increases and larger particles form via Ostwald ripening and coalescence. The film grows preferentially in the β-CuSCN phase. Additionally, a small fraction of the α-CuSCN phase and defect sites form.<br
Keywords: solution atomic layer deposition; liquid phase; in situ IR spectroscopy; atomic force microscopy; copper thiocyanate; neural network; density functional theory

Reduction of Oxide Layers on Au(111): The Interplay between Reduction Rate, Dissolution, and Restructuring - Stumm, Corinna; Grau, Sebastian; Speck, Florian D.; Hilpert, Felix; Briega-Martos, Valentin; Mayrhofer, Karl; Cherevko, Serhiy; Brummel, Olaf; Libuda, Jörg (Journal of Physical Chemistry C, 2021)
Dissolution and redeposition processes determine the stability of electrode materials. In this work, we address these processes in situ during oxidation and subsequent reduction of Au(111) electrodes in an acidic electrolyte (0.1 M H2SO4). We used complementary techniques, namely, electrochemical scanning tunneling microscopy (EC-STM) and on-line inductively coupled plasma mass spectrometry (ICP-MS). We observed that the reduction rate distinctively influences dissolution and the resulting morphology of the surface. Slow reduction leads to formation of monoatomic holes with a diameter of 1-9 nm on the surface. Dissolved Au species formed during reduction are detected in the bulk electrolyte. During fast reduction, however, the formed holes are much smaller and additional two-dimensional Au islands are formed. Almost no dissolved Au was detected in the electrolyte during reduction. We assign the observed differences to competing processes, namely, diffusion of the dissolved Au species into the solution and direct renucleation of dissolved Au.
CRIS-Team WoS Importer:2021-11-12

Squeezing the Threshold of Metal-Halide Perovskite Micro-Crystal Lasers Grown by Solution Epitaxy - Zhou, Shuyu; Rehm, Viktor; Afify, Hany A.; Feng, Yufei; Korczak, Jędrzej; Szczerbakow, Andrzej; Story, Tomasz; Peng, Zijian; These, Albert; Barabash, Anastasia; Osvet, Andres; Brabec, Christoph; et al. (Advanced Functional Materials, 2024)
Metal halide perovskite semiconductors have demonstrated remarkable progress not only in photovoltaics and X-ray detection but also in laser technologies. Particularly appealing is the simplicity with which micro-crystallites can be epitaxially grown, thereby forming micro-resonators suitable for lasing. Here, the laser threshold is optimized by selecting excitation laser parameters and by improving material quality. The latter process is conducted for formamidinium lead tribromide, emitting in the green spectral range. Depending on the growth method and parameters, the sizes of the micro-resonators can be tuned between ≈3 and 23 micrometers. Under laser excitation systematically lower thresholds are observed for micro-resonators in the 4–7 micrometer size range, than for larger ones, irrespective of growth method. Among three optimized growth methods, epitaxial growth via antisolvent vapor-assisted crystallization exhibits the smallest threshold powers, indicating the highest material quality. This conclusion is supported by hyperspectral microscopic luminescence imaging and by transient photoluminescence. The best laser structures exhibit record threshold powers for epitaxially grown perovskites, indicating that the selected antisolvent vapor epitaxial growth holds great promises also for other perovskite materials.
CRIS-Team Scopus Importer:2024-05-10
Keywords: FAPbBr; lasing; micro-resonators; perovskites; solution epitaxy